Formative Research in the Digital Context and Academic Competence in their Academic Works of University Students - Flores-Mamani , Emilio; Inquilla-Mamani, Juan; Apaza-Ticona, Jorge; Rojas-Salazar , Arcelia Olga; Alanoca-Arocutipa, Vicente; Guevara , Ronny Andree Chacon; Rojas , Félix Huanca (Journal of Ecohumanism, 2024)
Traditional teaching methodologies, such as lectures, are not the most effective in improving students' academic competence. However, through learning through formative research and the use of educational technologies, university students can better develop their academic competencies. The objective of this article was to determine the relationship between formative research in the context of dynamic digital technology and the academic competence of students at the Universidad Nacional del Altiplano in Peru. The methodology used was quantitative, cross-sectional and correlational. A survey was applied in the three areas of professional training, such as: social sciences, biomedical and engineering, to a representative sample of 382 students of both sexes, out of a population of 17,000 students. The findings of the research revealed a moderate positive relationship (r = 0.469), with a significance level of (p value = 0.00 < 0.05). This indicates that formative research, using various dynamic didactic techniques, is directly related to the academic competence of students in the elaboration of their academic works.